ANALISIS PENERAPAN TEKNOLOGI BUILDING INFORMATION MODELLING (BIM) PADA TAHAP PERENCANAAN GEDUNG SNOWDON TOWERS JAKARTA: Studi kasus: (PT. Razasa Karya) - Sihotang, Harlen; Sibarani, Peterson; Endi M Mulia (LPPM ISTP, 2025)
As a technology applied in infrastructure development, Building Information Modeling (BIM) makes construction modeling easier by providing data and tools that support planning, application and operation more efficiently and effectively. This research aims to assess the performance of BIM implementation at the project planning stage at PT. Razasa Karya, with a focus on the planning process for the construction of the Snowdon Towers Jakarta Building which consists of 6 floors, based on regulatory aspects for the procurement of goods and services. PT Razasa Karya focuses on engineering consulting services, project management, business development, and providing engineering consulting services. The research method used is qualitative with library observations which include Procurement TOR (Work Terms of Reference) data, Design and Build work contracts, and product planning such as Basic Design and more specifically Engineering Design (DED). The results of this research provide an increase in digital work efficiency and productivity, which aims to reduce various risks such as negligence, errors and communication problems in the field, by providing design visibility and better data management. In addition, applying BIM in the planning phase can increase time efficiency, budget, project cycle duration, and work quality by considering contracts for the supply of goods and services.